The Utilization of Bunker Eggs into Duck Feed in Tanjung Rejo Village, Deli Serdang Regency - Mayang Sari Yeanny; Masitta Tanjung (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The community service activities with the title "The Utilization of Bunker Eggs into Duck Feed in Tanjung Rejo Village, Deli Serdang Regency" will be held in May - November 2019. This activity aim is to convert bunker eggs (eggs that failed to hatch) into duck feed which has economic value and is environmentally friendly. The method used is counselling, lectures and training as well as monitoring and evaluation with the community directly to the field.The stages of duck feed production include; (1) choosing a bunker egg (2) egg waste is put into cormorant and boiled for approximately 1 hour, (3) cut water hyacinth/kale, (4) rice bran and water hyacinth/kale steamed into cormorant II which has been filled with water for approximately more than 1 hour, (5) bunker eggs, rice bran, and water hyacinth/kale are removed and drained in large containers and sacks, (6) bunker eggs are mashed without peeling the skin, (7) mixed all ingredients (endhog bunker, bran, kale) by adding enough water and stir until evenly distributed, (8) milling the mixture of materials using a special grinding to form feed, and (9) finishing includes the drying process using an oven/stove. Egg bunkers can be converted into animal feed